2017
DOI: 10.1016/j.immuni.2017.03.016
|View full text |Cite
|
Sign up to set email alerts
|

NAIP-NLRC4 Inflammasomes Coordinate Intestinal Epithelial Cell Expulsion with Eicosanoid and IL-18 Release via Activation of Caspase-1 and -8

Abstract: Summary Intestinal epithelial cells (IECs) form a critical barrier against pathogen invasion. By generation of mice in which inflammasome expression is restricted to IECs, we describe a coordinated epithelium-intrinsic inflammasome response in vivo. This response was sufficient to protect against Salmonella tissue invasion, and involved a previously reported IEC expulsion that was coordinated with lipid mediator and cytokine production, and lytic IEC death. Excessive inflammasome activation in IECs was suffici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

44
473
2
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 344 publications
(524 citation statements)
references
References 51 publications
44
473
2
5
Order By: Relevance
“…Nlrp3 −/− , Pycard −/− , Casp11 −/− , Casp1 −/− Casp11 −/− (He et al, 2016), Nlrp6 −/− (Chen et al, 2011), Il18 −/− (Seregin et al, 2017), Aim2 −/− , Il1b −/− (Seo et al, 2015), Casp1 −/− (Man et al, 2017), and Gsdmd −/− mice (Rauch et al, 2017) on C57BL/6 background have been reported. C57BL/6 WT and Ifnar1 −/− (Muller et al, 1994) mice were purchased from Jackson Laboratories.…”
Section: Star Methodsmentioning
confidence: 99%
“…Nlrp3 −/− , Pycard −/− , Casp11 −/− , Casp1 −/− Casp11 −/− (He et al, 2016), Nlrp6 −/− (Chen et al, 2011), Il18 −/− (Seregin et al, 2017), Aim2 −/− , Il1b −/− (Seo et al, 2015), Casp1 −/− (Man et al, 2017), and Gsdmd −/− mice (Rauch et al, 2017) on C57BL/6 background have been reported. C57BL/6 WT and Ifnar1 −/− (Muller et al, 1994) mice were purchased from Jackson Laboratories.…”
Section: Star Methodsmentioning
confidence: 99%
“…Inflammasome activation has also been implicated in expulsion of intestinal epithelial cells (IECs) from the intestinal epithelium prior to pyroptosis in response to microbial infection. While gasdermin D is required for pyroptosis but dispensable for expulsion of IECs[25], the possibility remains that other gasdermins may play a role in IEC expulsion, either alone or with redundancy.…”
Section: Gasdermin D Pores Are the Effectors Of Pyroptosismentioning
confidence: 99%
“…Recently, a specialized host defense role of the NLRC4 inflammasome was identified in mouse intestinal epithelial cells (IECs). Upon detection of Salmonella within IEC cytoplasm, the NLRC4 inflammasome rapidly forms producing IL-18 and diarrhea-causing eicosanoids (19). Instead of pyroptosis, Salmonella containing IECs undergo IL-18 independent, caspase dependent, non-lytic cell death with subsequent expulsion into the colonic lumen (20).…”
Section: Nlrc4 Inflammasome Biologymentioning
confidence: 99%
“…A growing literature links the intestinal ecosystem with NLRC4 activation and IL-18 production (19,20,28,42). As such, early gut colonization may promote excessive IL-1 family cytokine production in AIFEC patients.…”
Section: Treatment Of Nlrc4 Inflammasomopathiesmentioning
confidence: 99%